Censoring of autoreactive B cell development by the pre-B cell receptor - Keenan, Rebecca A.; De Riva, Alessandra; Corleis, Bjorn; Hepburn, Lucy; Licence, Steve; Winkler, Thomas; Martensson, Inga-Lill (Science, 2008)
Antibody diversity occurs randomly as B cells recombine their immunoglobulin (Ig) heavy- and light-chain genes during development. This process inevitably generates reactivity against self structures, and several mechanisms prevent the development of autoreactive B cells. We report here a role for the pre-B cell receptor, composed of Ig heavy and surrogate light chains, in the negative selection of cells expressing Ig heavy chains with the potential to generate autoantibodies. Surrogate light-chain-deficient (SLC ) mice harbored elevated levels of antinuclear antibodies (ANAs) in their serum and showed evidence of escape of pre-B cells expressing prototypic autoantibody heavy chains from negative selection, leading to mature autoantibody secreting CD21CD23 B cells in the periphery. Thus, the pre-B cell receptor appears to censor the development of certain autoantibody-secreting cells and may represent an important factor in multifactorial autoimmune diseases.